Microscopic characteristics of late intraocular lens opacifications - Kanclerz, Piotr; Yildirim, Timur Mert; Khoramnia, Ramin (Archives of pathology & laboratory medicine, 2021)
The increases in overall life expectancy and in lens surgeries performed on younger patients have resulted in a significant increase in the anticipated duration of artificial intraocular lenses (IOLs) in the eye. Thus, the physicochemical properties of the IOL become a critical issue, and several types of postoperative IOL opacifications have been reported.To describe the microscopic characteristics of opacified IOLs. Glistenings and subsurface nanoglistenings are fluid-related phenomena developing mainly in hydrophobic acrylic IOLs and are associated with aqueous influx into the IOL matrix. Calcification presents in hydrophilic acrylic or silicone IOLs as deposits of hydroxyapatite or other phases of calcium. Snowflake degeneration is less common, and it manifests in older polymethyl methacrylate IOLs.PubMed and ScienceDirect databases were searched for the following keywords: intraocular lens, IOL, cataract surgery, phacoemulsification, opacification, glistening, subsurface nanoglistenings, calcification, snowflake degeneration. English-language articles published up to October 15, 2019 were included in the study. The manuscript contains mainly a literature review; however, it was supplemented with original investigations from the David J. Apple International Laboratory for Ocular Pathology.Glistenings and subsurface nanoglistenings should be evaluated in a hydrated state and at room temperature; they manifest as microvacuoles sized from 1.0 to greater than 25.0 μm and less than 200 nm, respectively. Calcification deposits are situated on or underneath the surface of the IOL and can be stained with a 1% alizarin red solution or with the von Kossa method. Snowflake degeneration manifests as “particles” or “crystals,” causing whitish IOL discoloration. Scanning electron microscopy or energy dispersive X-ray spectroscopy may improve the diagnostic accuracy.